Application of graphene and its derivatives in cementitious materials: An overview. (15th April 2023) - Yang, Haibin; Zheng, Dapeng; Tang, Waiching; Bao, Xiaohua; Cui, Hongzhi
Abstract: Graphene and its derivatives (GD) have attracted extensive attention in the field of cementitious materials (CM) owing to their exceptional mechanical properties and functionalities. To date, many studies concerning the dispersion of GD in an alkaline environment of a cement matrix and the performance of graphene and its derivatives-based cementitious materials (GD/CM), including workability, mechanical properties, durability, and multi-functional characteristics, have been reported. There are both similar and controversial results in existing studies because researchers have conducted investigations from different perspectives. Therefore, it is necessary to summarize and review the latest research progress to provide a clear understanding of the influence of the performance and mechanism of GD in CM. In particular, the reinforcing mechanisms of GD are critically discussed and analyzed in this review to complement the existing literature on ambiguity in some underlying mechanisms. In addition, the main challenges of current research are highlighted, and recommendations are provided to guide future research in relevant fields. Highlights: Dispersion methods of GD in the alkaline environment are reviewed. Reinforcing mechanisms of GD in CM are summarized. The cost and environmental impacts of GD/CM are discussed. Key challenges and recommendations for future investigation are provided.